Evaluation of the genetic diversity of Huperzia serrate by rapd markers - Huong, Ho Thi; Linh, Ngo Thi Thuy; Anh, Le Thi Lan; Thuy, Le Thi Bich (Academia Journal of Biology, 2019)
Huperzia serrata, a valuable pharmaceutical plant distributed in Lao Cai (Northwest Vietnam) and Lam Dong (Central Highlands of Vietnam), is known as pharmaceutical materials for the treatment of Alzheimer’s disease. As a result of over-exploitation and habitat fragmentation, H. serrata has become a threatened plant in Vietnam, China and other countries around the world. For the understanding of population dynamics, adaptation, evolution and conservation of plant species in general and H. serrata in particular, the evaluation of genetic diversity is very important. In this study, a total of sixteen RAPD primers were used for evaluation of the genetic diversity of eight  H. serrata samples collected from different locations of Sa Pa and Da Lat. Overall, sixteen markers generated a total of 70 fragments in 8 collected samples of H. serrata. Of seventy generated fragments, 44 were found to be polymorphic. The number of fragments of each primer ranged from 1 to 8 with an average of 4,4 fragments per primer. The OPB20 primer revealed the highest polymorphism, while the OPB15, OPB17 and OPC12 primers gave the lowest. Polymorphism information content (PIC) values varied from 0.5266 to 0.8624 with an average of 0.7182, in which the highest value belonged to OPB11 primer while the OPC10 primer showed the lowest PIC value. The dendrogram created based on RAPD data sheet divided the investigated strain into two major groups corresponding to their habitat: Group I included three Da Lat samples (DL1, DL2, DL3) and Group II consisted of five samples from Sa Pa (SP1, Sp2, SP3, Sp4, and SP5). The results of our study could be useful for the conservation and development of H. serrata.